The energy-growth nexus in Malaysia: Does energy security matter? - Dzul Hadzwan, Husaini; Hooi, Hooi Lean (Elsevier Inc., 2026)
Insecure energy supplies, along with variations in other factor costs, have an impact on total production costs and eventually lead to a cost disadvantage among producers. This, in turn, greatly affects the trajectory of national economic growth. The aim of this study is to investigate the role of energy security in driving economic growth in Malaysia. The study employs an annual time series data of Malaysia from 1980 to 2018. The Auto-Regressive Distributed Lag approach has been employed to compute the long-run estimation. The results show that energy security has a positive relationship with economic growth. It should be noted that the magnitude and sign of the signal varies across all dimensions. This study recommends establishing an advanced renewable energy system with a larger generation scale and more widespread transmission and distribution. This will improve energy security by reducing dependence on both imported energy and unsustainable energy sources.